Aluminum-based boron carbide composite material for shielding neutrons and preparation method of aluminum-based boron carbide composite material
By distributing carbon nanotubes wrapped in aluminum powder around boron carbide particles, high-energy helium ions are blocked, the problem of helium bubble formation in boron carbide aluminum-based composite materials is solved, and the neutron shielding effect and mechanical properties of the material are improved.
Patent Information
- Application Number
- CN202411938546.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-26
AI Technical Summary
After the neutron absorption of the existing boron carbide aluminum composite materials, high-energy helium ions gather inside the material to form bubbles, resulting in a decrease in material performance and shortened service life.
Aluminum-based boron carbide composite material is formed by distributing carbon nanotubes around boron carbide particles and wrapping the carbon nanotubes in aluminum powder. Carbon nanotubes block high-energy helium ions in the near-interface micro-region of boron carbide particles, preventing them from entering the aluminum matrix, and reducing the formation of helium bubbles.
Effectively block high-energy helium ions, reduce the density of helium bubbles in the aluminum matrix, improve the neutron shielding effect and mechanical properties of the material, and extend the service life of the material.
Smart Images

Figure CN119736511A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of neutron absorbing materials and aluminum-based composite materials, and provides an aluminum-based boron carbide composite material for shielding neutrons and a preparation method thereof. Background Art
[0002] Boron carbide (B4C) is widely used in nuclear fuel storage containers due to its good neutron absorption ability. In addition, due to its advantages of low density and high specific strength, boron carbide is also often used as a reinforcement for aluminum-based composites. Therefore, the prepared boron carbide reinforced aluminum-based composites have excellent neutron absorption ability and mechanical properties at the same time, and have been widely used around the world.
[0003] The neutron absorption ability of B4C is mainly due to the isotope 10 B has an ultra-high neutron absorption cross section (3837Barn), and has the characteristics of wide neutron capture energy spectrum, no radioactive isotope production after decay, low secondary radiation energy, and high temperature resistance. 10 B captures a neutron and the following reaction occurs:
[0004] 10 B+n= 7 Li+ 4 He(500KeV)+2.78Mev
[0005] After the transmutation reaction, 10 B will release 4 He ions are released, and the released He ions will nucleate, agglomerate, grow and exist in the material as He bubbles. The size of the bubbles will increase with the increase of irradiation dose, and eventually form huge hole defects, which will affect the neutron shielding effect and mechanical properties of the device and affect its service life.
[0006] Patent document CN 116516200 A discloses a boron carbide aluminum-based composite neutron shielding material and a preparation method thereof. The boron carbide aluminum-based composite material adopts micron-grade powder and nano-grade carbide, and adopts mixed sintering and deformation processing and other processes to achieve a good neutron shielding effect. Among them, the nano-carbide can attract the He atoms generated after B4C absorbs neutrons to preferentially aggregate. However, although the nano-carbide has the ability to attract and adsorb He bubbles, the helium bubbles dispersed in the composite matrix will still aggregate and grow at the grain boundaries and phase boundaries of the aluminum matrix, forming larger bubbles and defects, causing great damage to the material properties. Summary of the invention
[0007] In view of the above problems, the present invention provides a neutron shielding aluminum-based boron carbide composite material and a preparation method thereof. The aluminum-based boron carbide composite material is composed of boron carbide particles, carbon nanotubes, and an aluminum matrix. The carbon nanotubes are wrapped by aluminum powder and distributed in the near-interface micro-region around the boron carbide particles, and the distribution range is within a space sphere of about 1 to 4 microns outside the boron carbide particles.
[0008] The technical solution of the present invention is as follows:
[0009] A method for preparing a neutron shielding aluminum-based boron carbide composite material comprises the following steps:
[0010] 1) mixing carbon nanotubes with aluminum-based powder A, so that the carbon nanotubes are wrapped on the aluminum-based powder A to obtain carbon nanotube-aluminum powder;
[0011] 2) low-speed ball milling of carbon nanotube-aluminum powder to obtain carbon nanotube / aluminum composite powder;
[0012] 3) high-speed ball milling of carbon nanotube / aluminum composite powder and boron carbide particles to obtain carbon nanotube / aluminum-coated boron carbide composite powder;
[0013] 4) dispersing and compounding the carbon nanotube / aluminum-wrapped boron carbide composite powder with the aluminum-based powder B to obtain a boron carbide-carbon nanotube / aluminum mixed powder;
[0014] 5) The boron carbide-carbon nanotube / aluminum mixed powder is pressed, sintered, and deformed to obtain the aluminum-based boron carbide composite material for shielding neutrons; the aluminum-based powder A and the aluminum-based powder B have different particle sizes.
[0015] In step 1), the particle size of the aluminum-based powder A is 5-10 μm.
[0016] In step 4), the particle size of the aluminum-based powder B is 20-50 μm.
[0017] In step 1), the inner diameter of the carbon nanotube is 10-30 nm, and the outer diameter of the carbon nanotube is 30-70 nm.
[0018] In step 3), the particle size of the boron carbide particles is in the range of 1 to 500 μm. The preferred particle size is in the range of 5 to 40 μm. More preferably, the particle size is in the range of 20 to 30 μm.
[0019] In step 1), the mass ratio of carbon nanotubes to aluminum-based powder A is 1:4-1:8.
[0020] In step 3), the mass ratio of carbon nanotube / aluminum composite powder to boron carbide particles is 1:1-1:3.
[0021] In step 4), the mass ratio of carbon nanotube / aluminum-wrapped boron carbide composite powder to aluminum-based powder B is 1:3-1:7.
[0022] In step 1), the powder mixing conditions are: 1600-2000rpm, and the time is 15-20min.
[0023] In step 2), the low-speed ball milling conditions are: ball-to-material ratio is 15-25:1; 80-120rpm.
[0024] In step 2), the abrasive balls used in ball milling are zirconia balls with a diameter of 6-10 mm.
[0025] In step 3), the high-speed ball milling conditions are: ball-to-material ratio of 10-20:1, 300-500 rpm, ball milling time of 1-3 hours, and the grinding balls are zirconia balls with a diameter of 6-10 mm.
[0026] In step 4), the carbon nanotube / aluminum-boron carbide composite powder and the aluminum-based powder B are dispersed and composited by one or more of mechanical mixing, variable speed ball milling, high-speed stirring mixing or air flow mixing.
[0027] Preferably, in step 4), the carbon nanotube / aluminum-boron carbide composite powder and the aluminum-based powder B are dispersed and composited by variable speed ball milling; the variable speed ball milling conditions are: first low speed 100 rpm ball milling for 3-4 hours, and then high speed 200 rpm ball milling for 2-3 hours.
[0028] In step 5), the carbon nanotube / aluminum-boron carbide composite powder is pressed by molding, cold isostatic pressing of powder or encapsulation.
[0029] In step 5), the sintering is performed by one or more of vacuum sintering, atmosphere protection sintering, hot pressing sintering, and hot isostatic pressing sintering.
[0030] In step 5), the sintering temperature is 500-650° C. and the sintering time is 0.1-10 h.
[0031] The aluminum matrix includes one or more of pure aluminum, 1 series aluminum alloy, 2 series aluminum alloy, 5 series aluminum alloy, 6 series aluminum alloy, and 7 series aluminum alloy.
[0032] In step 3), the deformation process adopts extrusion, rolling, forging, ring forging or spinning method.
[0033] The neutron shielding aluminum-based boron carbide composite material prepared by the method described above also belongs to the protection scope of the present invention.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) In the present invention, the role of the boron carbide particles is to absorb neutrons, and the role of the carbon nanotubes is to block the high-energy helium ions emitted from the boron carbide particles. The carbon nanotubes have excellent specific strength and specific modulus, and their own structure is stable, and they are effective blocking materials for high-energy helium ions. The energy of the high-energy helium ions emitted in the reaction of boron carbide absorbing neutrons is about 500 KeV. According to the calculation of the SRIM (Stopping and Range of Ions in Matter) program, the stopping distance of 500 KeV incident helium ions in the aluminum-based boron carbide composite material is 0 to 3 μm. The use of aluminum sheets to cover the carbon nanotubes at 0 to 6 μm near the interface microregion of the boron carbide particles can effectively block the high-energy helium ions from entering the composite matrix and causing structural damage.
[0036] (2) As a one-dimensional nanostructure, carbon nanotubes have a high specific surface area and high surface adsorption, and can absorb irradiated high-energy helium ions. Helium ions stagnant in the micro-region of the boron carbide interface tend to gather into helium bubbles and enter the core of the carbon nanotube through the carbon nanotube / aluminum interface. At this time, the carbon nanotubes wrapped in the outer interface of the boron carbide can serve as an effective storage space for helium bubbles, preventing them from entering the interior of the aluminum matrix, thereby reducing the helium density inside the aluminum matrix, reducing internal damage to the aluminum matrix, and ensuring material performance.
[0037] (3) Nano-sized carbon nanotubes also have the function of absorbing internal defects of materials. In aluminum-based boron carbide composite materials, defects formed in the material will preferentially migrate and recombine near carbon nanotubes, and finally be absorbed by carbon nanotubes. Carbon nanotubes uniformly dispersed near boron carbide particles help reduce the defect density at the interface between boron carbide and aluminum matrix, thereby improving the plasticity of the composite material.
[0038] (4) The dispersion of carbon nanotubes in the near-interface microregion of boron carbide aluminum-based composites enhances the material's dispersion strengthening ability, improves the material's mechanical properties, and is beneficial to the lightweight design of the material.
[0039] (5) The preparation method adopts powder metallurgy technology, which is suitable for the forming and processing of aluminum-based composite materials with different reinforcement mass fractions (5 to 40 wt.%) and large-scale component products, and can be used in neutron shielding application scenarios such as ground spent fuel storage and transportation, spacecraft nuclear-powered aircraft, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0041] Figure 1 This is a schematic diagram of the structure of the aluminum-based boron carbide composite material for shielding neutrons according to the present invention;
[0042] Figure 2The microstructure morphology of boron carbide, carbon nanotubes and aluminum matrix of the sample of Example 1 under a transmission electron microscope, wherein (a) is the distribution microstructure of boron carbide in the aluminum matrix; the enlarged blue box in (b) is a microscopic picture of the distribution morphology of carbon nanotubes inside the aluminum matrix, and the marked CNT is (Carbon Nano-tubes) carbon nanotubes. DETAILED DESCRIPTION
[0043] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0044] Figure 1 This is a schematic diagram of the structure of a neutron shielding aluminum-based boron carbide composite material of the present invention.
[0045] Example 1
[0046] The present embodiment provides a neutron shielding aluminum-based boron carbide composite material, which is a composite material composed of 10 wt.% boron carbide particles, 1 wt.% carbon nanotubes and a pure aluminum matrix.
[0047] The particle size of boron carbide is 20 μm;
[0048] The inner diameter of the carbon nanotubes is 10 nm (diameter range 10-30 nm), the outer diameter is 50 nm (diameter range 30-70 nm), and the average length is 2 μm (length range 1-5 μm);
[0049] The pure aluminum matrix is 5 μm pure aluminum powder and 30 μm pure aluminum powder with a purity of 99.9%.
[0050] The method for preparing the neutron shielding aluminum-based boron carbide composite material comprises the following steps:
[0051] Step 1) 10g of carbon nanotubes and 40g of aluminum powder with a particle size of 5μm are mixed and treated using a mechanical fusion modification machine, model NOB-130, using the centrifugal force generated by the high-speed rotating rotor in the equipment and the gravity of the material itself to wrap the small-sized material (carbon nanotubes) onto the large-sized material (micron aluminum powder), with a rated speed of 1600 rpm and a time of 15 minutes to prepare carbon nanotube-aluminum powder.
[0052] Step 2) The carbon nanotube-aluminum powder in step 1) is subjected to low-speed ball milling using a planetary ball mill with a rated speed of 100 rpm for 3 hours to prepare a carbon nanotube / aluminum composite powder; wherein the ball-to-material ratio is 20:1; the abrasive balls are zirconium oxide balls with a diameter of about 8 mm; at this time, the micron aluminum powder has been flaked, and the carbon nanotubes are attached to the flaky aluminum powder.
[0053] Step 3) adding 100 g of boron carbide particles to 50 g of the carbon nanotube / aluminum composite powder prepared in step 2), high-speed ball milling at 200 rpm for 2 hours to prepare a carbon nanotube / aluminum-encapsulated boron carbide composite powder; wherein the ball-to-material ratio is 15:1; the abrasive ball is a zirconium oxide ball with a diameter of about 8 mm; at this time, the carbon nanotube / aluminum mixed powder prepared in step 2) adheres to the boron carbide particles to form a coating layer.
[0054] Step 4) adding 850 g of aluminum powder with a particle size of 30 μm to the 150 g of carbon nanotube / aluminum-coated boron carbide composite powder prepared in step 3), and continuing the ball milling process, first at a low speed of 100 rpm for 3 hours, and then at a high speed of 200 rpm for 2 hours, to prepare a boron carbide-carbon nanotube / aluminum mixed powder;
[0055] Step 5) 1 kg of the boron carbide-carbon nanotube / aluminum mixed powder is pressed into an ingot with a diameter of 80 mm under a pressure of 180 tons, sintered at 520° C. for 3 hours for densification, and extruded into a 50 mm×10 mm plate to obtain a dense neutron shielding aluminum-based boron carbide composite material.
[0056] Figure 2 The microstructure morphology of boron carbide, carbon nanotubes and aluminum matrix of the sample of this embodiment under a transmission electron microscope, wherein (a) is the distribution microstructure of boron carbide in the aluminum matrix; the enlarged blue frame in (b) is a microscopic picture of the distribution morphology of carbon nanotubes inside the aluminum matrix, and the marked CNT is (Carbon Nano-tubes) carbon nanotubes.
[0057] After being wrapped by aluminum powder, the carbon nanotubes are distributed in the near-interface micro-region around the boron carbide particles, and the distribution range is within a space sphere of about 0 to 6 microns outside the boron carbide particles.
[0058] Example 2
[0059] The material specifications are the same as those in Example 1, and the preparation method is as follows:
[0060] Step 1) 8 g of carbon nanotubes and 37 g of aluminum powder with a particle size of 8 μm are mixed and treated using a mechanical fusion modification machine, model NOB-130, using the centrifugal force generated by the high-speed rotating rotor in the equipment and the gravity of the material itself to wrap the small-sized material (carbon nanotubes) onto the large-sized material (micron aluminum powder). The rated speed is 1800 rpm and the time is 18 minutes to prepare carbon nanotube-aluminum powder.
[0061] Step 2) The carbon nanotube-aluminum powder in step 1) is subjected to low-speed ball milling using a planetary ball mill with a rated speed of 110 rpm for 2.5 hours to prepare a carbon nanotube / aluminum composite powder; wherein the ball-to-material ratio is 22:1; the abrasive balls are zirconium oxide balls with a diameter of about 9 mm; at this time, the micron aluminum powder has been flaked, and the carbon nanotubes are attached to the flaky aluminum powder.
[0062] Step 3) Add 90g of boron carbide particles to 45g of carbon nanotube / aluminum composite powder prepared in step 2), and high-speed ball milling at 400 rpm for 2 hours to prepare carbon nanotube / aluminum-encapsulated boron carbide composite powder; wherein the ball-to-material ratio is 18:1; the abrasive ball is a zirconium oxide ball with a diameter of about 9mm; at this time, the carbon nanotube / aluminum mixed powder prepared in step 2) adheres to the boron carbide particles to form a coating layer.
[0063] Step 4) Add 865 g of aluminum powder with a particle size of 35 μm to 135 g of the carbon nanotube / aluminum-coated boron carbide composite powder prepared in step 3), and continue ball milling, first at a low speed of 100 rpm for 3.5 hours, and then at a high speed of 200 rpm for 2.5 hours to prepare a boron carbide-carbon nanotube / aluminum mixed powder.
[0064] Step 5) 1 kg of the boron carbide-carbon nanotube / aluminum mixed powder is pressed into an ingot with a diameter of 85 mm under a pressure of 190 tons, sintered at 580° C. for 2 hours for densification, and extruded into a 45 mm×12 mm plate to obtain a dense neutron shielding aluminum-based boron carbide composite material.
[0065] Comparative Example 1
[0066] The difference between this comparative example and Example 1 is:
[0067] The amount of materials used is the same, that is, a composite material composed of 10wt.% boron carbide particles, 1wt.% carbon nanotubes and pure aluminum matrix. The boron carbide particles have a specification of 20μm; the carbon nanotubes have an inner diameter of 10nm (diameter range 10-30nm), an outer diameter of 50nm (diameter range 30-70nm), and an average length of 2μm (length range 1-5μm); the matrix is 5μm and 30μm pure aluminum powder with a purity of 99.9%.
[0068] The preparation steps are different from those in Example 1; in this comparative example, the specific preparation steps are as follows:
[0069] Step 1) According to the above ratio, 10 g of carbon nanotubes and 890 g of aluminum powder are co-milled, wherein the 890 g of aluminum powder contains 40 g of 5 μm aluminum powder and 850 g of 30 μm aluminum powder, at 100 rpm for 4 hours to prepare graphitized carbon nanotube / aluminum composite powder;
[0070] Step 2) adding 100 g of boron carbide particles to the carbon nanotube / aluminum composite powder, first blending at a low speed of 100 rpm for 3 hours, and then ball milling at a high speed of 200 rpm for 2 hours to prepare a boron carbide-carbon nanotube / aluminum mixed powder;
[0071] Step 3) The boron carbide-graphitized carbon nanotube / aluminum mixed powder is pressed into an ingot with a diameter of 80 mm under a pressure of 180 tons, sintered at 550° C. for 3 hours for densification, and extruded into a 50 mm×10 mm plate to obtain a boron carbide-graphitized carbon nanotube / aluminum composite material.
[0072] Comparative Example 2
[0073] The difference between this comparative example and Example 1 is that the carbon nanotube content is different. The mass fraction of the carbon nanotubes used is 2 wt.%, that is, in this comparative example, step 1) adds 20 g of carbon nanotubes and 30 g of aluminum powder with a diameter of 5 μm to mix, and the subsequent steps remain unchanged.
[0074] Comparative Example 3
[0075] The difference between this comparative example and Example 1 is:
[0076] The materials used are consistent, i.e., a composite material composed of 10wt.% boron carbide particles, 1wt.% carbon nanotubes and a pure aluminum matrix. The boron carbide particles have a specification of 20μm; the carbon nanotubes have an inner diameter of 10nm (diameter range 10-30nm), an outer diameter of 50nm (diameter range 30-70nm), and an average length of 2μm (length range 1-5μm); the pure aluminum matrix is 5μm pure aluminum powder and 30μm pure aluminum powder with a purity of 99.9%.
[0077] The preparation steps are different from those in Example 1; in this comparative example, the specific preparation steps are as follows:
[0078] Step 1) 10 g of carbon nanotubes, 100 g of boron carbide and 890 g of aluminum powder (including 40 g of 5 μm aluminum powder and 850 g of 30 μm aluminum powder) are mixed according to the above ratio using a high-speed mechanical mixing device, wherein the rated speed is 1600 rpm and the rated time is 20 minutes;
[0079] Step 2) The mixed powder in step 1) is placed in a planetary ball mill for ball milling. The ball mill speed is 200 rpm, the ball milling time is 3 hours, the ball-to-material ratio is 20:1, and 8 mm zirconia balls are used.
[0080] Comparative Example 4
[0081] The difference between this comparative example and Example 1 is that in step 1), the 5 μm aluminum powder is replaced with 30 μm aluminum powder.
[0082] Comparative Example 5
[0083] The difference between this comparative example and Example 1 is that no carbon nanotubes are added, and the aluminum-based boron carbide composite material of this comparative example is a composite material composed of 10 wt.% boron carbide particles and a pure aluminum matrix.
[0084] Performance Testing
[0085] 1. Mechanical properties test
[0086] A universal materials testing machine (Instron Model 3344) equipped with a static axial clamp-on extensometer (Instron Model 2630-101) was used to test the -4 s -1 The composite material was subjected to a uniaxial tensile test at room temperature at a constant loading rate of . The specimen size, shape and test method were carried out in accordance with GB / T 228.1-2010 "Room Temperature Test Method for Tensile Test of Metallic Materials". A circular tensile specimen was used with a gauge length of 25 mm and a diameter of 5 mm. For the tensile specimen, a specimen with the tensile axis parallel to the extrusion direction was first cut from the extruded sheet using wire cutting, and then the surface of the parallel section of the specimen was polished with fine sandpaper (1200 mesh) to remove surface oil and other dirt to obtain a smooth surface specimen.
[0087] Ion irradiation: The dose of ion implantation is 3×10 17 ions / cm -2 In the helium ion implantation experiment, before the ion implantation, the sample was sampled from the extruded sheet of the aluminum-based composite material by wire cutting along the plane perpendicular to the extrusion direction. After sampling, it was first ground and polished, and then annealed to ensure a smooth surface and eliminate processing defects.
[0088] Table 1
[0089]
[0090] Microscopic characterization: Field emission transmission electron microscopy (TEM) was used to capture the material morphology, high-resolution images (HRTEM) and high-angle annular dark field images (HAADF) to characterize and analyze the boron carbide particles and carbon nanotubes in the interface microregion of the composite material. The model was FEI Talos F200X G2, and the acceleration voltage was 200KV.
[0091] Table 2
[0092]
[0093]
[0094] Figure 2 The microstructure morphology of boron carbide, carbon nanotubes and aluminum matrix of the product of Example 2 under a transmission electron microscope, wherein a) is the distribution microstructure of boron carbide in the aluminum matrix; b) is an enlargement of the blue box in a), which is a microscopic picture of the distribution morphology of carbon nanotubes inside the aluminum matrix, and the marked CNT is (Carbon Nano-tubes) carbon nanotubes.
[0095] The aluminum-based boron carbide composite material consists of boron carbide particles, carbon nanotubes, and an aluminum matrix. The carbon nanotubes are distributed in a near-interface microregion within about 0-6 microns outside the boron carbide particles, and the size of the carbon nanotube layer wrapped in the near-interface microregion of the boron carbide is controlled by adjusting the mass fraction of the doped carbon nanotubes, and finally a spherical composite reinforcement body in which the carbon nanotubes wrap the boron carbide particles in the aluminum matrix is formed; the boron carbide particles absorb neutrons, and the carbon nanotubes block and absorb helium, a byproduct of the neutron reaction, from entering the aluminum matrix, so that the formation of aggregated helium bubbles inside the aluminum matrix to affect the material properties is avoided, and the comprehensive properties such as neutron shielding, radiation damage resistance, and mechanical strength are improved.
[0096] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art can make various changes or modifications within the scope of the claims, which does not affect the essence of the present invention. In the absence of conflict, the embodiments of the present application and the features in the embodiments can be combined with each other arbitrarily.
Claims
1. A method for preparing a neutron shielding aluminum-based boron carbide composite material, characterized in that: The steps include: 1) mixing carbon nanotubes with aluminum-based powder A, so that the carbon nanotubes are wrapped on the aluminum-based powder A to obtain carbon nanotube-aluminum powder; 2) low-speed ball milling of carbon nanotube-aluminum powder to obtain carbon nanotube / aluminum composite powder; 3) high-speed ball milling of carbon nanotube / aluminum composite powder and boron carbide particles to obtain carbon nanotube / aluminum-coated boron carbide composite powder; 4) dispersing and compounding the carbon nanotube / aluminum-wrapped boron carbide composite powder with the aluminum-based powder B to obtain a boron carbide-carbon nanotube / aluminum mixed powder; 5) Pressing, sintering and deforming the boron carbide-carbon nanotube / aluminum mixed powder to obtain the carbon nanotube / boron carbide aluminum-based composite material; The aluminum-based powder A and the aluminum-based powder B have different particle sizes.
2. The preparation method according to claim 1, characterized in that: In step 1), the particle size of the aluminum-based powder A is 5-10 μm; And / or, the particle size of the aluminum-based powder B is 20-50 μm.
3. The preparation method according to claim 1, characterized in that: In step 1), the inner diameter of the carbon nanotube is 10-30 nm, and the outer diameter of the carbon nanotube is 30-70 nm; And / or, in step 3), the particle size of the boron carbide particles ranges from 1 to 500 μm.
4. The preparation method according to claim 1, characterized in that: In step 1), the mass ratio of carbon nanotubes to aluminum-based powder A is 1:4-1:8; And / or, in step 3), the mass ratio of carbon nanotube / aluminum composite powder to boron carbide particles is 1:1-1:3; And / or, in step 4), the mass ratio of carbon nanotube / aluminum-wrapped boron carbide composite powder to aluminum-based powder B is 1:3-1:
7.
5. The preparation method according to claim 1, characterized in that: In step 1), the powder mixing conditions are: 1600-2000 rpm, time is 15-20 min; And / or, in step 2), the low-speed ball milling conditions are: ball-to-material ratio is 15-25:1; 80-120rpm; And / or, in step 2), the abrasive balls used in ball milling are zirconia balls with a diameter of 6-10 mm; And / or, in step 3), the high-speed ball milling conditions are: ball-to-material ratio of 10-20:1, 300-500 rpm, ball milling time of 1-3 hours, and the grinding balls are zirconia balls with a diameter of 6-10 mm.
6. The preparation method according to claim 1, characterized in that: In step 4), the carbon nanotube / aluminum-boron carbide composite powder and the aluminum-based powder B are dispersed and composited by one or more of mechanical mixing, variable speed ball milling, high-speed stirring mixing, and air flow mixing.
7. The preparation method according to claim 6, characterized in that: The carbon nanotube / aluminum-boron carbide composite powder and the aluminum powder are dispersed and composited by variable speed ball milling; the variable speed ball milling conditions are: firstly low speed 100-150 rpm ball milling for 3-4 hours, and then high speed 200-500 rpm ball milling for 2-3 hours.
8. The preparation method according to claim 1, characterized in that: In step 5), the carbon nanotube / aluminum-boron carbide composite powder is pressed by molding, cold isostatic pressing of powder or encapsulation; And / or, in step 5), the sintering is carried out by one or more of vacuum sintering, atmosphere protection sintering, hot pressing sintering, and hot isostatic pressing sintering; the sintering temperature is 500-650° C. and the time is 0.1-10 h.
9. The preparation method according to claim 1, characterized in that: The aluminum-based powder A and the aluminum-based powder B are selected from one or more of pure aluminum, 1 series aluminum alloy, 2 series aluminum alloy, 5 series aluminum alloy, 6 series aluminum alloy, and 7 series aluminum alloy.
10. A neutron shielding aluminum-based boron carbide composite material prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Powder metallurgy preparation method of carbon nanotube reinforced aluminum alloy composite material
CN103789564A
Preparation method of aluminum-based composite material
CN110744047A
Carbon nanotube / aluminum composite material and preparation method thereof
CN110938764A
Preparation method of nano-carbide reinforced aluminum matrix composite welding wire
CN112593110A
Nanometer aluminum oxide reinforced aluminum-based boron carbide, preparation method thereof and neutron absorbing material
CN114959410A